'Feeling of despair' as the leading cluster theme of conceptual descriptive analyses in participatory assessment: Russia Oxfam GB case study. Issue 4 (1st December 2016) - Zakirova, Venera; Zakus, David
Abstract : This article provides a case study on participatory assessment based on experience gained from an EU–Oxfam GB project entitled "Empowering Municipalities to Effectively Address Poverty" conducted in five small towns in Russia. Participatory assessment through focus group discussions (FGDs) was the main approach used in the implementation of the project. A participatory assessment was performed through 25 FGDs in five remote areas in central Russia. More than 200 participants representing people living in poverty, such as single mothers, people with disabilities, families with many children, families with disabled children, and pensioners, voluntarily participated in the meetings. Most of the participants were women (75%) aged between 25 and 70 years. We consider that the participants' representation is relevant in accordance with the official poverty studies. Through identification of patterns of recurrent ideas and opinions, a qualitative method helps us understand social phenomena from the views of and on the basis of the opinions of the participants. The FGDs' narratives underwent pattern analysis, resulting in the framing of the cluster themes and narrative conceptualization. Cluster analysis of the FGDs' narratives led to the framing of 10 cluster themes of importance, followed by conceptual descriptions and related narratives. The conceptual description of the leading theme, feeling of despair (theme 1), was described by respondents' expressions/narratives, such as "Nobody needs us and there is no future for us and our children in this town, " the narrative idea that crosscuts the subsequent themes. The following nine themes are of equal importance, are interlinked, and for the major part constitute the leading theme, feeling of despair (theme 1): state social and family support (theme 2); health care (theme 3); who are those living in poverty? (theme 4); housing (theme 5); living costs (theme 6); employment (theme 7); children's well-being and future (theme 8); environment and recreation (theme 9); and legal rights (theme 10). Equal importance of these themes is justified by the analysis of patterns and recurrence of the FGDs' narrative ideas. The assigned numbers from 2 to 10 are given to simplify the references to the corresponding cluster throughout the analysis and do not reflect the ranks of the clusters. The leading theme (theme 1) touches on the psychological status of the FGDs' participants, while the remaining nine themes (themes 2–10) relate to the state system of social services, including health care. For example, per the conceptual descriptions, the state social and family support (theme 2) is described by the following narrative: "Those who have a family network get their support, for those without family help, state support is crucial but is very little and not everybody can get it. Nobody wants to help or provide decent services – people in local government get fed up with you, you get sent from one place to another." The frustration ("Nobody wants to help or provide decent services; the government gets fed up with you, you get sent from one place to another.") caused by poor services ("State support is crucial but is very little and not everybody can get it.") crosscuts the theme's conceptual description. In this article, feeling of despair refers to a psychosocial condition caused by people living in poverty and their dissatisfaction with state services. Details of the remaining themes are given. The purpose of this article is to draw the attention of practitioners and policy makers to the participatory results rather than their focusing on the qualitative methodological details. We argue that a participatory understanding of community needs, through cluster theme analysis and conceptual descriptions, can help local municipalities develop more targeted community programs on poverty and vulnerability reduction.